Nowotwór jako metafora: Susan Sontag i Oriana Fallaci. Pamięci Wiesławy Kłosek = Cancer as a metaphor: Susan Sontag and Oriana Fallaci. In memory of Wiesława Kłosek - Tichoniuk-Wawrowicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The essay, dedicated to the memory of Wiesława Kłosek, analyzes the metaphorics of cancer in the writings of Susan Sontag and Oriana Fallaci, authors who were themselves oncological patients and wrote with strong emotions. Sontag called for dealing with the gloomy mythologization of cancer; Fallaci, on the other hand, fought the taboo of this disease while simultaneously reaching for stigmatizing metaphors of cancer.
Keywords: nowotwór; rak; choroba; pacjent; metaforyka; mit; cancer; carcinoma; disease; patient; metaphor; myth